Dynamic spatio-temporal patterns and driving factors of green waste generation based on provincial panel data in China - Song, Boyao; Han, Xiao; Li, Yueying; Huang, Wenjin; Fang, Qiushuang; Ren, Xueyong; Li, Hongxun (Frontiers in Environmental Science, 2025)
IntroductionGreen waste is the second largest organic solid waste beyond of household waste in Chinese cities. Clarifying green waste generation is significant for efficient management and utilization.MethodsUnlike previous studies that mainly concentrated on quantifying green waste at a single time point and within a particular region, this research is grounded in the urban greening data of 30 provinces in China spanning from 2003 to 2022. It systematically computes and analyzes the overall green waste generation scenario and its spatio - temporal distribution traits in China. Moreover, it innovatively employs the adjusted IPAT - LMDI (Environmental Impact = Population × Affluence × Technology - Logarithmic Mean Divisia Index) model to probe into the key driving factors influencing green waste production.Results and DiscussionsResearch has found that: 1) From 2003 to 2022, the total amount of landscaping waste resources in China showed an overall upward trend, with a total of 10.7134 million tons in 2003 and an increase of nearly 5 times to 60.9705 million tons in 2022; 2) The overall density of resource generation shows a fluctuating upward trend, with a characteristic of high in the east and low in the west, gradually evolving into high in the southeast and low in the northwest; 3) The factors of population size, economic development, and environmental pressure all have a positive driving effect on the total increase of green waste resources, but urban development shows a negative effect of decreasing the number of green waste resources; 4) Anticipated against the backdrop of global warming, urban sprawl, and improving urban green space management standards, China’s green waste production is projected to persistently rise, with forecasting an increase to between 83.35 million and 91.48 million tons in total by 2030. Although this study has achieved some progress in quantifying and analyzing the spatial - temporal characteristics and driving forces of China’s green waste, there is still room for further improvement in terms of research accuracy and scope in future studies.